Biophysiological responses of premature infants in neonatal nursing care: a descriptive study of infant and maternal characteristics - Dwi Hastuti; Anggorowati Anggorowati; Zubaidah Zubaidah; Tri Nur Kristina; Siti Yuyun Rahayu Fitri (International Journal of Public Health Science (IJPHS), 2026)
Preterm infants are physiologically vulnerable and require continuous cardiorespiratory and thermal monitoring during neonatal nursing care. Evidence describing physiological indicators in relation to infant maturity and maternal sociodemographic characteristics remains limited. This study aimed to describe physiological indicators (heart rate, respiratory rate, oxygen saturation, and temperature) among preterm infants and examine their associations with infant and maternal characteristics. An observational descriptive study was conducted from August to December 2025 among preterm infants (